Digital culture and the information regime: Political governance in times of democratic system crisis - Villalobos-Antúnez, José Vicente; Guerrero-Lobo, José Francisco; Martin-Fiorino, Víctor; Astudillo-Campusano, Pamela; Caldera Ynfante, Jesús Enrique (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The information regime is mediated by the culture of the electronic device. It is characterized by the control of the deluded citizen through the deployment of freedom, thereby nullifying the core issue of human life: freedom. Through phenomenological-hermeneutic methodology (Heidegger, 2002), this work starts from the world of digital life to direct the interpretation towards digital governance, all of which appears as a hermeneutic horizon the information regime. It is concluded that in this new social order the political and all other orders that arise from interaction are governed by a capitalism of emotions.